2013
DOI: 10.3329/fmcj.v8i1.16894
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Need for Family Planning among Married Women: Experience from Rural and Urban Communities

Abstract: :Unmet need for family planning is the key indicator to achieve Millennium Development Goal by the year 2015. Bangladesh Government has a great success in family planning sector but population has almost doubled in recent years. This study was carried out among married women to compare the determinants of unmet need for family planning among rural and urban communities during the period from July 2010 to June 2011. Unmet need for family planning in rural community was found 18(12%) and in urban community it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…In this study, injectable, implant and IUD users were 15.8%, 5.6% and 4.4% respectively; these findings were consistent with similar studies 6,16 . Almost half of the respondents got information about contraceptives from the family planning workers this finding conforms with other similar studies 8,14 in Bangladesh.…”
Section: Contraceptive Statussupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, injectable, implant and IUD users were 15.8%, 5.6% and 4.4% respectively; these findings were consistent with similar studies 6,16 . Almost half of the respondents got information about contraceptives from the family planning workers this finding conforms with other similar studies 8,14 in Bangladesh.…”
Section: Contraceptive Statussupporting
confidence: 93%
“…From this study, it revealed is that male partners are not only taking less responsibility for contraceptive use but also some cases they are barring to use contraceptives. This study also reveals that misconception about the side effects and religious factors also barring to use contraceptives; this finding consistent with other studies 6,12 .…”
Section: Contraceptive Statussupporting
confidence: 91%
See 1 more Smart Citation
“…If the population increases at this rate, it will create a great challenge on our economy. To overcome this problem of population explosion, government as well as the NGOs has introduced the concept of family planning among the people 5 . Due to their great achievement in this field, currently the contraceptive prevalence rate (CPR) has increased manifold 6 .…”
Section: Introductionmentioning
confidence: 99%